2019
DOI: 10.24251/hicss.2019.050
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Development of a Cloud-based Platform Supporting Team-oriented Evidence-based Reasoning: SWARM Systems Paper

Abstract: The Smartly-assembled Wiki-style Argument Marshalling project (SWARM) commenced in 2017 as part of the US Intelligence Advanced Research Projects Activity (IARPA) funded Crowdsourcing Evidence, Argumentation, Thinking and Evaluation (CREATE) Program. The SWARM project has developed an online platform allowing groups to produce evidence-based reasoning. This paper provides a summary of the core requirements and rationale that have driven the SWARM platform implementation. We present the technical architecture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The role of crowd-sourced intelligence and its classification within traditional or new parameters, is itself an active research topic (Stottlemyre, 2015). Recently, the IARPA CREATE project (IARPA, 2017) led the development of the SWARM Systems (Sinnott et al, 2019), a collection of platforms for integrating analytics techniques and informal argumentation to support analysis through crowd-sourced intelligence. The SWARM interface provides a portal which combines capabilities of question-answering platforms and shared document editing systems.…”
Section: Information Requirements Crowdsourcing and Social Sensingmentioning
confidence: 99%
“…The role of crowd-sourced intelligence and its classification within traditional or new parameters, is itself an active research topic (Stottlemyre, 2015). Recently, the IARPA CREATE project (IARPA, 2017) led the development of the SWARM Systems (Sinnott et al, 2019), a collection of platforms for integrating analytics techniques and informal argumentation to support analysis through crowd-sourced intelligence. The SWARM interface provides a portal which combines capabilities of question-answering platforms and shared document editing systems.…”
Section: Information Requirements Crowdsourcing and Social Sensingmentioning
confidence: 99%
“…The platform enables “contending analyses” through a process of sharing resources and draft reports, feedback and rating, and group selection of high‐quality contributions (van Gelder & Rozario 2018). Important elements of the SWARM process include an initial period of anonymity to manage social dominance effects and recognising the need to create “social warmth” (Sinnott et al 2019, p. 412). The SWARM platform relies on mutual encouragement and shared credit for collaboration, which functions to support interaction between users and the refinement of contending ideas.…”
Section: Collaborative Reasoning Platformmentioning
confidence: 99%
“…SWARM supports the combination of Q&Astyle crowdsourcing and Contending Analyses with a cloud platform incorporating a distinctive user interface (Sinnott et al, 2019), shown in Figure 1.…”
Section: Swarm Interfacementioning
confidence: 99%